Polymer-mediated nanorod self-assembly predicted by dissipative particle dynamics simulations. Issue 34 (14th September 2015) - Khani, Shaghayegh; Jamali, Safa; Boromand, Arman; Hore, Michael J. A.; Maia, Joao
<x xml:space="preserve">Abstract</x> Three dimensional phase diagram for controlled aggregation/dispersion of polymer grafted nano-rods in a polymer matrix.